El MMPI (Español) aplicada a jóvenes mexicanos: Influencias de sexo, edad y nivel de inteligencia - Navarro, Roberto (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study was designed to evaluate the effects of sex, age, and intelligence on the 13 basic MMPI scale T-scores. A Spanish version of the MMPI was used on a sample of relatively normal young Mexicans. Data included the MMPI (Spanish) and the Dominós Test scores (for intelligence levels) from 144 males and 144 females 14 to 25 years old. Major findings from the ANOVA were that (a) men’s T-scores differed significantly from women’s on Scales L, K, 2, 3, 5, 7, 7, 9, and 0, (b) significant age level effects (which were larger than sex effects) were found for Scales L, F, K, 3, 7, 8, 9, and 0, and (c) Scale 5 was the only one significantly affected by intelligence levels.